Inovasi Biskuit Biosuplemen Kelinci (BBCi) Berbasis Sampah Organik Wilayah Perkotaan Di Desa Ngronggo Kota Kediri - Mubarak Akbar; Efi Rokhana; Diah AW. Kusumatutie (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Densely populated settlements in the Kediri have their own problems in the livestock sector. Starting from the problem of narrow land for raising livestock and the availability of feed. Raising rabbits is one of the ways of the Sumber Rejeki livestock group, Ngronggo Village, Kediri City so that they can continue to raise livestock. The ability of rabbits to use various types of feed makes it easier for rabbits to be kept, especially in urban areas by utilizing the potential of local feed resources. However, farmers are still lacking information about local urban waste that can be used to feed rabbits as well as how to prepare rabbit rations. The solutions that can be given are counseling on the types of local feed ingredients that can be used as rabbit feed and training on forage handling and how to prepare complete rations for rabbits. The methods used in this community service are participatory, outreach, mentoring, and training for partner group members and there will be an evaluation at the end of the activity. The resulting output is an increase in the understanding of farmers about local animal feed ingredients and an increase in the ability to prepare rabbit rations. The resulting product is in the form of feed as biscuits,it’s easy to bite because rabbits are rodents. This feed product will later be referred as rabbits biosupplement biscuit.